Sexual disorders beyond DSM-5: the unfinished affaire. Issue 6 (November 2017) - Navarro-Cremades, Felipe; Simonelli, Chiara; Montejo, Angel L.
Abstract : Purpose of review: To provide an overview of post-The Diagnostic and Statistical Manual of Mental Disorders, 5th ed. classifications related to human sexuality. After reviewing the literature on classification and clinical practice of sexual disorders, some of the most important contributions on main sexological classifications and frameworks were selected, especially from January 2016 till June 2017. Recent findings: New relevant contributions on psychiatric and sexological classifications and frameworks have been proposed, such as the international classification of diseases 11th revision (ICD-11), research domain criteria, the third edition of the Diagnostic Manual in Sexology and the person-centered psychiatry perspective. Summary: ICD-11 proposals regarding conditions related to sexual health including sexual dysfunctions and gender incongruence as well as vaginismus, such as sexual pain disorder, paraphilic disorders as mental Disorders. The disorders associated with sexual development and orientation, are proposed for deletion. The other perspectives aforementioned are also presented.